Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/w12082279
|View full text |Cite
|
Sign up to set email alerts
|

Which Aspects of Hydrological Regime in Mid-Latitude Montane Basins Are Affected by Climate Change?

Abstract: This study analyzed the long-term alterations in runoff regime, seasonality and variability in headwater montane basins in Central Europe in response to the manifestations of climate change. We tested the common hypotheses on climate change effects on surface runoff dynamics in the Central Europe region, assuming that (i) recent climate warming will result in shifts in the seasonality of runoff, (ii) the runoff balance will remain without significant changes and (iii) that higher variability in runoff can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…(MOD, HOR), the change was negligible suggesting that the ratio between summer and winter low flows remained almost the same at these sites throughout the 1968-2019 period. The relative stability of these two catchments during the study period is supported by the lowest average temperatures and the largest proportion of snow cover influencing the summer low flows [18,54], indicating that the warming has not significantly influenced the overall runoff balance of most montane catchments yet [12,27]. However, multiple studies suggest a further decrease in snow cover depth and snow water equivalent in montane areas of Central Europe, leading to a decrease in snowmelt contribution to summer runoff in the near future [27,31].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(MOD, HOR), the change was negligible suggesting that the ratio between summer and winter low flows remained almost the same at these sites throughout the 1968-2019 period. The relative stability of these two catchments during the study period is supported by the lowest average temperatures and the largest proportion of snow cover influencing the summer low flows [18,54], indicating that the warming has not significantly influenced the overall runoff balance of most montane catchments yet [12,27]. However, multiple studies suggest a further decrease in snow cover depth and snow water equivalent in montane areas of Central Europe, leading to a decrease in snowmelt contribution to summer runoff in the near future [27,31].…”
Section: Discussionmentioning
confidence: 97%
“…The increasing frequency, intensity and duration of streamflow droughts in mid-latitudes of the Northern Hemisphere represent some of the predicted effects of climate change [6][7][8]. In the context of increasing severity of droughts in Europe during the last decade [9][10][11], the effects of climate change on runoff regime will very likely affect the runoff seasonality, variability of discharge and also the risk of extreme streamflow drought occurrence [12,13]. Under conditions of rising air temperature, increasing evaporation rates, decreasing soil-moisture [14][15][16] and decreasing snow cover in the Central European region [17][18][19], the droughts are more likely to occur and escalate into multiyear events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This water abundance together with the ability of mountainous catchments to redistribute water originating from snow from previous seasons (Carroll et al 2019;Cochand et al 2019) is why mountains are often referred to as "water towers" (Viviroli et al 2007). As these regions are highly susceptible to changes in hydrological behaviour due to changes in both air temperature and precipitation patterns (Sorg et al 2012;Langhammer and Bernsteinová 2020;Vlach et al 2020) it is vital to investigate how these changes manifest themselves in the abundance or deficiency of water within the streams.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers in the SI were focused on the impact of climate change on the change of groundwater regime [7] and subsequently on the change of hydrological properties of soils [8]. The authors [9] confirmed in the regions of Central Europe as well as in the Netherlands [10] significant shifts in runoff seasonality, coinciding with the timing of the air temperature rise, marked by earlier snow-melt, followed by a decline in spring flows and a prolonged period of low flows. The progressive built-up area-the impermeability of the landscape-can also have an indirect effect on the hydrological regime.…”
mentioning
confidence: 97%